Sleeve gastrectomy in patients with obesity - Todurov, I. M.; Plehutsa, O. I.; Perekhrestenko, O. V.; Kalashnikov, O. O.; Kosiukhno, S. V. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Obesity is one of the most common chronic diseases in the world, described by the World Health Organization as "a non-infectious epidemic of the late XX - early XXI century." One of the ways to solve this problem was the rapid development of so-called weight correction surgery - bariatric surgery. One of the most progressive and effective techniques of the modern era has been the sleeve gastrectomy. Objective. To study the immediate and long-term results of open and laparoscopic sleeve gastrectomy in Ukraine in patients with obesity. Methods. Analysis of surgical treatment of 117 patients with obesity, who underwent sleeve-gastrectomy (from a laparoscopic approach – 59 (50,4%) patients, from a supramedian laparotomic approach – 58 (49,6%) patients) was performed. Results. The performance of sleeve gastrectomy provided an effective loss of excess body weight. Mean EBWL 2 years after surgery was 68.9 ± 7.6%. Complete compensation of arterial hypertension, dyslipidemia and type 2 diabetes was achieved in 60 (72.3%), 51 (68.9%) and 17 (65.4%) patients, respectively. In the remaining patients, there was a significant regression of the severity of the concomitant diseases with the possibility of effective control of the blood pressure level due to monotherapy, improvement of the lipidogram indices. Partial remission of type 2 diabetes was recorded in 9 (34.5%) patients. Conclusion. Sleeve gastrectomy is an effective and safe technique for the surgical treatment of obesity, which provides a significant reduction in excess body weight and a regression of concomitant obesity-associated diseases and metabolic disorders.